Online cognitive-behavioral intervention for stress among English as a second language teachers: implications for school health policy - Eze, Angela; Anyebe, Mary O.; Nnamani, Rebecca G.; Nwaogaidu, John C.; Mmegwa, Patricia U.; Akubo, Esther A.; Bako, Victoria N.; Ishaya, Salome N.; Eze, Matthew I.; Ekwueme, Francis O.; Awokwe, Ngozi N.; Ekwueme, Uchechukwu H.; et al. (Frontiers in Psychiatry, 2023)
Stress is among the high ranked work-related injury all over the world, and has become almost general among the Nigerian workforce. English as second language (ESL) teachers face enormous work-related threats leading to occupational stress. When ESL teachers are stressed, the students' language development and entire educational progress are at risk. This is mostly underscored as English though a second language forms the language of instruction in Nigerian schools. As a result, managing occupational stress is particularly important in ESL teachers as such is among the sure ways of improving ESL learning and the overall educational outcomes. This study looked at the effectiveness of online cognitive behavioural intervention (o-CBI) in lowering occupational stress among ESL teachers. ESL teachers with at least one year of experience were among the participants (N=89). Participants were divided into two groups: intervention group (N=44) and control (N=45). For 9 weeks, the experimental group engaged in 9 sessions of 2 hours o-CBI program. The Single Item Stress Questionnaire (SISQ), Satisfaction with Therapy and Therapist Scale-Revised (STTS-R) and Teachers' Stress Inventory (TSI) were the measures used to collect primary and secondary data. Four sets of data were collected at baseline, post-test, as well as follow-up 1 and 2 evaluations. Data were analyzed using mean, standard deviation, t-test statistics, repeated measures ANOVA, and bar charts. When compared to the control group, the o-CBT group reduced significantly in their TSI scores at post-test (Time 2) and follow-up evaluations (Time 3 and 4). Between pre, post, and follow-up 1 and 2 measurements, there were no significant differences in occupational stress index scores of the control group. It was concluded that o-CBI is effective in job-stress treatment among ESL teachers. Implications for school health policy were discussed. The o-CBI for occupational stress was well received by the participants, showing high acceptability among of ESL teachers.